Headache in patients infected with the novel coronavirus (Covid-19): An integrative literature review - Bastos, Sarah Nilkece Mesquita Araújo Nogueira; Sousa, Diego Afonso Cardoso Macedo de; Melo, Simone Santos e Silva; Barbosa, Bárbara Louise Freire; Cruz, Larisse Giselle Barbosa; Silva-Néto, Raimundo Pereira (Headache Medicine, 2020)
Introduction: The disease caused by the new coronavirus was named by the acronym COVID- 19 which means “COrona VIrus Disease”, while “19” refers to the year 2019, when the first cases in Wuhan, China, were identified. Objective: Our objective was to identify the prevalence of headache and to know its clinical characteristics in COVID-19 patients, available in the literature. Methods: Based on a literature search in the major medical databases and using the descriptors “headache and coronavirus”, “headache and 2019-nCoV”, “headache and SARS- CoV-2”, “headache and coronavirus and 2019-nCoV” and “headache and coronavirus and SARS-CoV-2” we include articles published between January 2019 and April 2020. We found 94 articles, but only 13 met the inclusion criteria. Results: In 13 articles analyzed in this review, a total of 3,105 Chinese patients (51.6% men and 48.4% women) had laboratory diagnoses of COVID-19. In 240 (7.7%) patients, headache was an associated symptom of COVID-19, but in only 52 (21.7%) of them there was some information about the characteristics of this headache. Conclusions: COVID-19 patients have several clinical manifestations, including headache that is nonspecific with a prevalence of 7.7%.